2015
DOI: 10.5812/ircmj.26919v2
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Profile in Patients With Acute Coronary Syndrome

Abstract: Background:Thyroid hormone has the a major role in the cardiovascular system function and cardiac a As well as to maintain the cardiovascular homeostasis A slightly change ind thyroid status actually affects cardiovascular mortality hemodynamic. The background of this study was to define the prevalence of thyroid dysfunction in acute coronary syndrome (ACS).Objectives:The primary objective was to define the prevalence of thyroid dysfunction in acute coronary syndrome, including Non-ST Segment Elevation Myocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 34 publications
4
25
0
Order By: Relevance
“…The exact prevalence of the low T3 syndrome among patients suffering an ACS seems not to be clearly defined yet. A wide range from 5% to 35% has been reported in literature, and this could be attributed to differences in study populations between the conducted studies . However, the syndrome seems to occur more frequently in STEMI compared with NSTEMI patients, possibly because of their poorer early prognosis and the pathophysiologic features of the occlusive thrombus resulting in more myocardium at stake …”
Section: Thyroid Hormonal Alterations During Acsmentioning
confidence: 97%
See 1 more Smart Citation
“…The exact prevalence of the low T3 syndrome among patients suffering an ACS seems not to be clearly defined yet. A wide range from 5% to 35% has been reported in literature, and this could be attributed to differences in study populations between the conducted studies . However, the syndrome seems to occur more frequently in STEMI compared with NSTEMI patients, possibly because of their poorer early prognosis and the pathophysiologic features of the occlusive thrombus resulting in more myocardium at stake …”
Section: Thyroid Hormonal Alterations During Acsmentioning
confidence: 97%
“…Normal thyroid homeostasis seems to alter in a subgroup of patients with ACS. Several studies have observed a fall in total T3 and/or fT3 concentration and rise in rT3 concentration after an acute coronary event . The exact prevalence of the low T3 syndrome among patients suffering an ACS seems not to be clearly defined yet.…”
Section: Thyroid Hormonal Alterations During Acsmentioning
confidence: 99%
“…5 Additionally hypothyroidism is emerging as a risk for coronary artery disease. 6 Evaluation of thyroid hormone plasma levels has been done in a number of studies in patients presenting with Acute Coronary Syndrome (ACS) and findings compared between Unstable Angina/Non-ST elevation MI (UA/NSTEMI) and ST Elevation acute MI (STEMI) groups. 1,7 Some studies have reported association of greater hormonal changes with more severe cardiac events( STEMI and Death) and patients with complications.…”
Section: Introductionmentioning
confidence: 99%
“…1,7,8 An association of Euthyroid sick syndrome in ACS with poorer prognosis has been suggested in few studies. 1,6 It has further been stated that the euthyroid sick syndrome has special significance in patients of ACS because low T3 levels in these patients signify severe disease and can be used as a marker for early invasive management in these patients. 6 Till date to my knowledge there are no data regarding thyroid profile in ACS patients from this part of world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation